A Bibliometric Analysis of Global Trends in Engineering Education Research - Susilawati, Aay (ASEAN Journal of Educational Research and Technology, 2024)
Engineering education has emerged as a key driver of innovation and economic development in the 21st century. As global educational systems evolve, understanding the trajectory of research in engineering education becomes crucial for policy and curriculum reform. This study provides a comprehensive bibliometric analysis of global trends in engineering education research by examining 195,601 documents indexed in Scopus from 1877 to 2023 using the search string TITLE-ABS-KEY(engineering AND education). The analysis focused on annual publication trends, subject area distributions, and thematic evolution. Tools such as Microsoft Excel, VOSviewer, and Bibliometrix (R) were used for data processing and visualization. Results indicate exponential growth in publications from the early 2000s, with notable contributions from engineering, computer science, and social sciences. These findings highlight the interdisciplinary nature of engineering education and underscore the increasing attention to digital tools, pedagogical innovation, and policy development. The study contributes to strategic planning for future research directions in the field.